'Women's work and low pay', 1985 (1985)
1985 1960-2000 "'Women's work and low pay', 1985" [EP0042], 1985 'Women's work and low pay' is the report of the conference for women organised by the South East Region TUC [SERTUC] Women's Rights Committee and Centres for the Unemployed Women's Working Party on 13 July, 1985 at Congress House.